Uji Aktivitas Antihiperurisemia Ekstrak n-Heksana, Etil Asetat, dan Etanol 70% Daun Tempuyung (Sonchus arvensis L.) pada Mencit Jantan Hiperurisemia - Ferani Cendrianti; Siti Muslichah; Evi Umayah Ulfa (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
The purpose of this research was to study the activity of Sonchus arvensis leaves extract as antihyperuricemics agent on hyperuricemic male mice. Eighteen male mice were divided into six groups, i.e the first group as a normal control K(N); the second group as a negative control K(-) treated chicken liver juice 0,2 % b/v orally; the third group as a positive control K(+) treated allopurinol 10 mg/kg BW orally; the fourth to six groups P1, P2, and P3 were treated with nhexane, ethyl acetate, and ethanol 70% of Sonchus arvensis leaves extract 300 mg/kg BW orally for 4 days. Pottasium oxonate 300 mg/kg BW i.p was induced 1 hour before the blood samples was collected. The blood samples was taken from vena ophtalmicus. The concentration of uric acid was determined with FS DHBSA. Data was analyzed using one way ANOVA and LSD test. The result showed that activity of ethyl acetate and ethanol 70% extract of Sonchus arvensis leaves has significant effect in reducing the concentration of uric acid in hyperuricemic mice. Base on phytochemistry screening it has flavonoid and terpenoid. The substance that estimated has antihyperuricemic activity was flavonoid.